Prospects of carbon capture technologies for enhanced oil recovery in Nigeria’s oil and gas sector - Effiom, Precious-Chibuzor; O. Effiom, Samuel; E. Evareh , John; O. Uket, Igri; Osim-Asu, Dane (International Journal of Engineering and Technology, 2024)
Nigeria, a nation with abundance of natural resources, has over the years generated its major revenue from the export of crude oil, one of its leading natural resources, obtained from different Oil fields in various states of the country. Revenue generated from this export constitutes the greater percentage of the country’s gross domestic product (GDP) as a result of the local and international transactions involved in the transportation of this product. A good percentage of these Oil fields have been exploited while some are yet to be utilized. However, it has become an issue of great concern that approximately 40% of the original oil in place (OOIP) have not been recovered and hence allowed to fallow in the reservoir. Carbon (CO2) capture as an innovative technology to enhance the recovery of OOIP in Nigeria oilfields is proposed. Various oil recovery technologies as well as CO2 capture technologies were studied and their advantages outlined on how the latter can be significantly used in enhancing a greater percentage (40% - 60%) of oil recovery over a given period of time and fallow period. Technologies such as primary, secondary (chemical/binary) and tertiary oil recovery methods respectively, were reviewed. Oil recovery between 5 to 25% of OOIP, 6 to 40% of OOIP, and an additional (5 to 25) % totaling 40 to 60 % OOIP, were identified from primary, secondary, and tertiary oil recovery processes respectively. Conversely, modified CO2 injection EOR is suggested as a more suitable enhanced oil recovery (EOR) method for low-pressure reservoirs in Nigeria. Although it is capital intensive, CO2 capture for EOR have posed less threat to the atmosphere with an equivalent economic improvement and pollution reduction from studied literature.